Strongly Coupled Oxasmaragdyrin–BF2 Chelated Dipyrrin Dyads: Syntheses, X‐ray Structure, Ground‐ and Excited‐State Charge‐Transfer Interactions. Issue 7 (14th December 2016) - Gobeze, Habtom B.; Kumar, Sunit; D'Souza, Francis; Ravikanth, Mangalampalli
Abstract: Oxasmaragdyrin (osm), a 22‐π electron aromatic macrocycle containing four pyrroles and a furan ring connected by three methine bridges and two direct bonds is shown to be an excellent electron donor–sensitizer exhibiting adequate spectral and redox properties. Further, this novel heterocyclic macromolecule has been utilized in building donor–acceptor systems involving BF2 ‐chelated dipyrromethenes (BODIPYs). The osm–BODIPY dyads were fully characterized by optical, electrochemical, computational, and X‐ray diffraction studies. Due to close proximity and electronic structure of the donor and acceptor entities, strong intramolecular charge‐transfer interactions in these dyads was witnessed and was supported by computational studies. Solvent‐polarity‐dependent rapid charge separation and charge recombination in these dyads is witnessed from photochemical studies involving time‐resolved emission and femtosecond transient absorption studies. The present studies bring out the importance of oxasmaragdyrin as an electron donor in light‐energy‐harvesting artificial photosynthesis model systems. Abstract : Donor–acceptor interactions : Oxasmaragdyrin (osm), a 22‐π electron aromatic macrocycle, has been shown to be an efficient electron donor by newly synthesizing osm–BODIPY donor–acceptor dyads, and conducting studies involving time‐resolved emission and femtosecond transient absorption techniques.